Oncologic Panendoscopy: Description of an Optimized Procedure Based on Our Experience - Pincet, Laurence; Sandre, Cécile de; Lang, Florian J. W.; Colin, Victor (International Archives of Otorhinolaryngology, 2021)
Introduction All patients with a new head and neck squamous cell carcinoma (HNSCC) undergo diagnostic panendoscopy as part of the screening for synchronous second primary tumors. It includes a pharyngolaryngoscopy (PLS), a tracheobronchoscopy and esophagoscopy, and a stomatoscopy. Rigid techniques are risky, with long learning curves.Objective We propose a precise description of the panendoscopy protocol. We include an optimization of the PLS technique that completes the flexible esophagoscopy when rigid esophagoscopy isn't performed.Methods The present retrospective observational study includes 122 consecutive patients with a new primary HNSCC who underwent traditional panendoscopy and the new PLS technique between January 2014 and December 2016. A two-step procedure using a Macintosh laryngoscope and a 30° telescope first exposes panoramically the larynx, the upper trachea, and the oropharynx; then, in a second step, the hypopharynx is exposed down to the upper esophageal sphincter. Broncho-esophagoscopy is performed with a rigid and flexible scope.Results In total, 6 (5%) patients presented synchronous tumors (3 in the esophagus, 2 in the oral cavity, and 1 in the larynx 1). Rigid endoscopy was complicated by 2 (1,6%) dental lesions, and had to be completed with a flexible scope in 38 (33%) cases for exposition reasons. The two-step PLS offered a wide-angle view of the larynx, upper trachea, and oro- and hypopharynx down to the sphincter of the upper esophagus. The procedure was easy, reliable, safe, repeatable, and effectively completed the flexible endoscopies.Conclusion Rigid esophagoscopy remains a difficult procedure. Two-step PLS combined with flexible broncho-esophagoscopy offers good optical control.
Keywords: squamous cell carcinoma; esophagoscopic surgical procedure; cancer screening test; multiple primary neoplasms; synchronous; synchronous neoplasms